First isolation and molecular identification of Enterobacter hormaechei in a sheep production unit with respiratory syndrome from Northern Veracruz, Mexico - Huerta–Peña, Javier Cruz; Hernández–Carbajal, Gabriela Romina; Ballados–González, Gerardo Gabriel; Martínez–Hernández, José Manuel; Villagómez–Cortés, José Alfredo; Sanchez–Montes, Sokani (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
Sheep production in Mexico encounters notable challenges, among which infectious diseases stand out as a growing concern. Ovine respiratory syndrome (ORS) is particularly problematic, being a leading cause of economic losses in the industry. However, despite its significant negative impact, there remains a lack of comprehensive understanding regarding the microorganisms involved. For this reason, the aim of this study was to isolate and identify the causal agents responsible for a respiratory disease outbreak in a sheep production unit in Northern Veracruz. This included: collection of samples from affected sheep, focusing on those displaying clinical signs of respiratory illness; microbial culturing and molecular identification of the isolated bacteria. We isolated rounded, raised colonies with a pink mucoid aspect which were molecularly identified as Enterobacter hormaechei, which exhibited a similarity of 99.59% with sequences from China. The isolation and molecular identification of E. hormaechei provide new insights into the pathogens affecting sheep, highlighting the importance of continuous surveillance and research in improving sheep health and production. This study represents a significant step in identifying and understanding the causal agents of ORS in Northern Veracruz.